Effect of AVDR on load distribution law of high subsonic stator - Zhang, Zhuyu; Zhou, Zhenggui (Proceedings of SPIE, the international society for optical engineering, 2025)
Axial Velocity Density Ratio (AVDR) is an important parameter to check the two-dimensionality of cascade flows. In the present study, the effect of AVDR has been investigated on a high subsonic stator. An automatic optimization design method is used to obtain the optimal profile with different density ratio. Detailed Computational Fluid Dynamics (CFD) studies were carried out with different blade profiles under three different AVDRs and three different inlet Mach numbers. Key aerodynamic performance parameters and flow structure through the cascade were analyzed in detail. At zero Angle of attack, when the inlet Mach number is constant, the peak Mach number and position of each blade profile have no obvious change with the increase of AVDR, and the leading edge load decreases, while the middle and rear load gradually increases. With the increase of inlet Mach number, the peak Mach number of each blade increases gradually, but the position remains unchanged.